Estimated Number of People who Inject Drugs in Ho Chi Minh City, Vietnam: Findings from a Two-survey Capture-Recapture Population Size Estimation Exercise - Nghia Van Khuu; Phuc Duy Nguyen; Giang Tong Le; Hoa Thi Yen Luong; Van Thi Thu Tieu; Hau Phuc Tran; Thuong Vu Nguyen; Meade Morgan; Abu S. Abdul-Quader (Springer, 2020)
Background: HIV/AIDS program managers in Ho Chi Minh City (HCMC), Vietnam have always relied on the police reports and the UNAIDS Estimation and Projection Package for population size estimation of People Who Inject Drugs (PWID). Methods: We used Respondent-driven Sampling (RDS) to implement a two-source capture-recapture study to estimate the population size of PWID in HCMC in 2017. The study was implemented in seven out of 24 districts and included men and women ages 18 years and older who reported injecting illicit drugs in the last 90 days, and who had lived in the city for the past six months. Estimates of the PWID population size for each of the seven districts were calculated accounting for the RDS sampling design. These were then adjusted to account for the district sampling probabilities to give an estimate for HCMC. Chapman two-source capture-recapture estimates of population size, based on simple random sampling assumptions, were also calculated for comparison. Results: The estimates resulted in a population size for HCMC of 19,155 [95% Confidence Interval (CI): 17,006-25,039] using the RDS approach and 17,947 (95% CI: 15,968-19,928), using the Chapman approach. Conclusion: The two-survey capture-recapture exercise provided estimates of PWID in HCMC - based on Chapman estimator and RDS approach - are similar. For planning HIV prevention and care service needs among PWID in HCMC, both estimates may need to be taken into consideration together with size estimates from other sources.